Predictors of long‐term drug survival for infliximab in psoriasis. (21st June 2016) - Magis, Q.; Jullien, D.; Gaudy‐Marqueste, C.; Baumstark, K.; Viguier, M.; Bachelez, H.; Guibal, F.; Delaporte, E.; Karimova, E.; Montaudié, H.; Boye, T.; Aubin, F.; et al.
Abstract: Background: Limited information is available regarding factors associated with long‐term drug survival of infliximab for psoriasis in real life. Objectives: The main aim pf this study was to identify predictors of long‐term (>12 months) drug survival among patients treated with infliximab for psoriasis in a real‐world clinical setting. Methods: Retrospectively collected data, relating to disease, patient characteristics and treatment procedures, in a multicentre observational cohort of patients with moderate‐to‐severe plaque psoriasis treated with infliximab at eight university hospitals, 120 of whom maintained a response to infliximab for more than 12 months, were compared with prospectively collected data in the same centres from 54 patients who experienced secondary loss of response within a 12‐month period. Results: Mean duration of drug survival of infliximab in patients with long‐term drug survival was 41.12 months ± 20.64 SD vs. 8.5 months ± 2.43 SD in patients with a secondary loss of response. Multivariate analysis identified greater disease severity at treatment onset (PASI score >12) (OR = 5.18, 95% CI: 1.60–16.77, P = 0.006), high levels of initial psoriasis clearance (PASI‐90 reduction or equivalent) (OR = 18.50, 95% CI: 4.56–74.45, P = 0.0001) and combination with methotrexate (OR = 13.15, 95% CI: 1.46–118.79, P = 0.022) as independent predictors of long‐term drug survival and sustained efficacy of infliximab. Conclusion: Positive predictors for long‐term drug survival of infliximab in real life were identified. Their impact on treatment management should be addressed in further prospective trials.